The Relationship Of Premenopause Mother’s Knowledge And Attitudes With The Level Of Anxiety In Facing Menopause In Premenopause Employees - Devy Putri Nursanti; Eri Puji Kumalasari (Journal of Health Science Community, 2025)
Every woman will experience menopause, where menopause is the final stage of a woman’s reproductive period. Women who enter menopause will experience physical and psychological problems, if this is not handled properly it will cause anxiety, so sufficient knowledge and a positive attitude are needed. The aim of this research was to determine the relationship between knowledge and attitudes of premenopausal employees and anxiety levels in facing menopause. This type of research is quantitative with a cross sectional design. The sample in this research consisted of 31 respondents, namely employees aged 40-53 years who had not experienced menopause, obtained through purposive sampling. Data collection used a knowledge questionnaire, attitude questionnaire and anxiety questionnaire with the Zung Self rating Anxiety Scale (ZSAS). Data analysis using the Chi Square test. The research results show that the level of employee knowledge about menopause is in the good category (45.1%), and employees who have negative attitudes towards menopause are in the negative category (61.2%), and the level of anxiety is in the mild category (51.6%). There is a significant relationship between the knowledge of premenopausal employees in facing menopause with a value of p = 0.034, and there is a significant relationship between the attitude of premenopausal employees and the level of anxiety in facing menopause with a value of p = 0.017. Research sites can develop a PKRS program around menopause as a whole (patients, employees and visitors) either using print media or audio-visual media, so that education regarding changes during menopause can be easily and more easily accessible to patients, employees and visitors.